Orientation of the Carboxy-terminal Regions of Fibrin γ Chain Dimers Determined from the Crosslinked Products Formed in Mixtures of Fibrin, Fragment D, and Factor XIIIa - Siebenlist, Kevin R; Meh, David A; Wall, Joseph S; Hainfeld, James F; Mosesson, Michael W (Thrombosis and Haemostasis, 1995)
There are two schools of thought regarding the orientation of the intermolecular ∈-amino-(γ-glutamyl) lysine isopeptide bonds formed between γ chains in the D domains of assembled fibrin fibers. Some investigators believe that these bonds are oriented parallel to the direction of fiber growth (longitudinally) at the contacting ends of fibrin D domains (‘DD-long’), whereas others believe that these bonds are oriented across the two-stranded fibril, between D domains in opposing strands (‘DD-transverse’). To distinguish between these two possibilities, the structure of crosslinked products formed in mixtures of fibrin, plasmic fragment D, and factor XIIIa were analyzed, based upon this rationale: Complex formation between D fragments and a fibrin template depends upon the non-covalent ‘D:E’ interaction between each fibrin E domain and two D fragments (‘D:fibrin:D’). If carboxy-terminal γ chains in the D:fibrin:D complex become aligned in a DD-long configuration, only crosslinked fragment D dimers (‘D-D’) will result and the fibrin ‘template’ will not become crosslinked to the associated D fragments. If instead, γ chain crosslinks form transversely between the D fragments and fibrin, covalently linked D-fibrin complexes will result.SDS-PAGE of factor XIIIa crosslinked mixtures of fibrin and fragment D demonstrated products of a size and subunit composition indicating D-fibrin and D-fibrin-D formation. Small amounts of D dimers were also formed at the same levels as were formed in mixtures of fragment D and factor XIIIa alone. Electron microscopic images of D-fibrin-D complexes prepared under physiological buffer conditions demonstrated that the D fragments were associated with the central E domain of the fibrin molecule, but that they could be dissociated from this non-covalent association in 2% acetic acid. These findings indicate that γ chain crosslinks occur transversely in D:fibrin:D complexes and permit the extrapolated conclusion that γ chain crosslinks are also positioned transversely in an assembled fibrin polymer.